2 Answers | Add Yours
`therefore y=x+200` and `y=x+99 z` and `x+99z=x+200` from the given information. We first solve for z:
`therefore x-x+99z=200 `
`therefore 99z=200 `
`therefore z=200/99` and substituting into `y=x+99z` we get
`y=x+99(200/99)` (note that `99 times 200/99 = 200` )
`y=x+200` which we already have.
As this is the same equation leaving us with y=x+200 =x+200, we can only solve for x in terms of y:
`therefore x=y-200` . Other than that we cannot obtain a value for x without additional information.
To solve three variables: x,y and z; one needs atleast three equations. Hence this question cannot be solved further.
We’ve answered 319,661 questions. We can answer yours, too.Ask a question